Characterisation of novel strains of multiply antibiotic-resistant Salmonella recovered from poultry in Southern Senegal - Dione, Michel M; Geerts, Stanny; Antonio, Martin (The Journal of Infection in Developing Countries, 2011)
Introduction: Non-typhoidal Salmonella (NTS) contamination in poultry and poultry products is a major cause of food-borne disease in humans. This study presents the molecular epidemiology of NTS isolated from poultry in Senegal. Methodology: A total of 261 NTS recovered from broiler farms, chicken carcasses and street vendors were characterized using random amplification of polymorphic DNA (RAPD) and multilocus sequence typing (MLST) techniques. Results: We observed 20 distinct RAPD profiles corresponding to 18 different serotypes. Strains from each of these 20 groups were further analysed using MLST. Consequently, 12 new MLST alleles and 17 new sequence types were discovered. Three sequence types (S. Kentucky ST198, S. Agona ST13 and S. Istanbul ST33) have previously been described in Senegal and other countries, suggesting that these clones are geographically widely distributed and are circulating in a wide range of hosts. Nine clones showed multi-resistance to the most commonly used antibiotics in both humans and animals. However, a novel multi-resistant clone of S. Kentucky ST832 was found. Conclusion: This study gives new insights into the genetic diversity of NTS in Senegal. Molecular tools remain essential to improve our understanding of the epidemiology of NTS by tracking the sources of infection and/or contamination.